The Mozambican PRSP initiative: Moorings, usage and future - Lars Buur (Danish Institute for International Studies (DIIS), 2009)
This paper analyses the seemingly uncontroversial public life of the PRSP approach in Mozambique and suggests that it embodies much of the Frelimo government's thinking about development since independence, though obviously 'packaged' to fit international donor discourses as they continually change. The PRSP is therefore not an outright 'imposition' on the Frelimo government or necessarily a 'challenge' to its sovereignty, as it is often argued. In general we argue that the PRSP became over time a broad 'consensus document' because it came to potentially incorporate 'all' stakeholders needs and wishes. We argue that after the political turbulence of the 1980s and 1990s with privatisation and structural adjustments, the PRSP allowed for different elite groups to find common ground with regard to ideological and party-preserving concerns, as social and market-economic trade-offs could now be legitimately accommodated.
Keywords: 330; Wachstumspolitik; Armutspolitik; Entwicklungsstrategie; Mosambik